The Ac/N-Degron Domain of MARCHF6 E3 Ubiquitin Ligase and Its Role in Regulating Ferroptosis - Hope Omoniyi; Grace Hohman; Mohamed Eldeeb (Cells)
Ferroptosis is a form of cell death characterized by iron and reactive oxygen species accumulation. Notably, this mode of cell death has been shown to exhibit significant implications for aging-related disorders including tumorigenesis and neurodegeneration. Nonetheless, the intricate underlying molecular mechanisms of ferroptosis and their differential roles in the molecular etiology of these diseases are still elusive. Elucidating the precise molecular mechanisms underlying ferroptosis is, thus, important for understanding the molecular basis of these diseases and unveiling potential therapeutic targets. MARCHF6 is an E3 ub ligase involved in regulating various cellular processes throughout the cell including ferroptosis. Research findings by Yang et al. identified a novel role of MARCHF6 E3 ub ligase in recognizing Ac/N-degron bearing substrates, which includes pro-ferroptotic and anti-ferroptotic proteins, demonstrating a regulatory role for MARCHF6 in fine-tuning ferroptosis. Herein, we highlight these recent findings and discuss the potential role of MARCHF6 in modulating ferroptosis pointing to the emerging role of MARCHF6 as a potential therapeutic target for treating ferroptosis-related diseases.